PENGARUH SOCIAL MEDIA MARKETING DAN STORE ENVIRONMENT TERHADAP CUSTOMER RETENTION YANG DIMEDIASI OLEH PERCEIVED VALUE PADA KONSUMEN KOTTY KOSMETIK DI BANDA ACEH - Dwi Mustika; Farid Farid (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to measure the effect of Social Media Marketing and Store Environment on Customer Retention mediated by Perceived Value on Kotty Cosmetics consumers in Banda Aceh. The sample used in this study was Kotty Cosmetics consumers, totaling 200 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used is purposive sampling. Structural Equation Modeling (SEM) is used as an analytical method to determine the effect between the variables involved. Based on the results of SEM analysis it is identified that Social Media Marketing and Store Environment have a positive effect on Customer Retention, Social Media Marketing and Store Environment have a positive effect on Perceived Value, Perceived Value fully mediates the influence of Social Media Marketing on Customer Retention, and the influence of the Store Environment on Customer Retention.